TARGETED GENE SILENCING OF KRAS ONCOGENES IN PANCREATIC CANCER USING SIRNA-LOADED GOLD NANOPARTICLES - Shakib Ahmed; Zahidul Islam; Fatimah El Balqis (Journal of Biomedical and Techno Nanomaterials, 2025)
Pancreatic cancer, predominantly driven by mutations in the KRAS oncogene, remains one of the most lethal malignancies due to its resistance to conventional therapies. RNA interference (RNAi) using small interfering RNA (siRNA) presents a powerful strategy to silence oncogenes, but its clinical application is liited by the poor stability and inefficient delivery of naked siRNA. This study aimed to develop and validate a targeted nanodelivery system using gold nanoparticles (AuNPs) to efficiently deliver KRAS-specific siRNA and induce potent gene silencing in pancreatic cancer cells. A nanoconjugate was synthesized by attaching thiol-modified siRNA targeting the G12D-mutant KRAS gene to PEGylated gold nanoparticles. The physicochemical properties of the siRNA-AuNPs were characterized. The platform’s efficacy was evaluated in vitro using the PANC-1 human pancreatic cancer cell line. KRAS expression was quantified via qRT-PCR and Western blot, while cellular viability and apoptosis were assessed using MTT and flow cytometry assays, respectively. The synthesized siRNA-AuNPs exhibited excellent stability and were efficiently internalized by the cancer cells. This targeted delivery resulted in a significant downregulation of KRAS mRNA and protein expression by over 75% (p < 0.01) compared to controls. Consequently, this oncogene silencing led to a substantial inhibition of cancer cell proliferation and a marked increase in apoptosis. Gold nanoparticles serve as a highly effective and robust vector for the targeted delivery of siRNA. This nanomedicine platform successfully silences the critical KRAS oncogene, inducing cell death in pancreatic cancer cells and representing a promising new avenue for targeted cancer therapy.